Financial accounting - Williams, Jan R.; Haka, Susan F.; Bettner, Mark S.; Meigs, Robert F. (McGraw-Hill/Irwin, 2003)
Presents the "Management Strategy," "Your Turn" and "Case in Point" boxes throughout the chapters for business majors. This book also offers a grounding in accounting basics that prepares accounting majors for their intermediate accounting course. It uses video clips, animated graphics and Excel templates to demonstrate accounting concepts.